Scenario of Antibiotic Resistance in Pakistan: A Systematic Review - Sarwat Iqbal, Shahzad Majeed Bhatti, Muhammad Amir, Qamar Uz Zaman, Ayesha Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A rise in antimicrobial resistance and a decrease in the discovery of novel antibiotics have occurred in recent years. Pakistan is a South Asian developing nation with a high level of antibiotic resistance, which poses a serious regional and global threat. Objective: To determine the situation of antimicrobial resistance in Pakistan Methodology: In the current study the literature was reviewed systematically according to the guidelines of PRISMA. Numerous databases like PUBMED, Embase, Medline and Google scholar were reviewed to determine the prevalence of antimicrobial resistance in Pakistan in the last 10 years from 2012 to 2022. For collection of duplicate data, a standardized extractive datasheet was used. All the data was entered in Microsoft Excel 2019. Results: In the current study, a total of 82 articles were included for final analysis. Multiple drug resistant bacteria were observed in 8 (9.76%) studies while extensive drug resistant bacteria were observed in 2 (2.44%) studies. High median resistance (95% CI) was shown by E. coli to first line antibiotics. Salmonella spp showed high median resistance to ciprofloxacin (90.5%). High median resistance was observed to majority of available antibiotics by Acinetobacter spp. Pseudomonas spp were highly susceptible (86.5%) to cefoperazone-sulbactam. MRSA S. aureus was reported in 13 studies and they were highly resistant to penicillin (98%), cefoxitin (83%) and levofloxacin (80%). Conclusion: Our study concludes that antimicrobial resistance pattern of common pathogens was high against commonly prescribed antibiotics. Regularization of monitoring practices, regular local and national monitoring, molecular investigations, and particular efforts to address the risk associated with the rise in antibiotic resistance are required to combat this issue.